2021
DOI: 10.1016/j.jse.2021.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Histologic case series of human acellular dermal matrix in superior capsule reconstruction

Abstract: Background: Acellular dermal matrix (ADM) allografts are commonly used in the surgical treatment of complex and irreparable rotator cuff tears. Multiple studies report that superior capsule reconstruction (SCR) using ADM has resulted in short-term clinical success as assessed via radiographic and patient-reported outcomes. However, limited information is available regarding the biologic fate of these grafts in human subjects. This case series describes histologic results from 8 patients who had reoperations, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Soft tissue augmentation using the remaining rotator cuff tendon to enhance the biological healing response to the ADM also provided a biologic scaffold for graft bone healing and increased the strength of the reconstructed superior capsule. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Soft tissue augmentation using the remaining rotator cuff tendon to enhance the biological healing response to the ADM also provided a biologic scaffold for graft bone healing and increased the strength of the reconstructed superior capsule. 10 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, concerns about the limited biological potential of HDA have recently been addressed to some extent by a retrieval study from Lederman et al, which demonstrated that it is a "hospitable scaffold" for host cell infiltration and remodeling. 8 The authors reported that all grafts had evidence of cellular infiltration, neovascularisation, and active remodeling. Furthermore, in a rabbit model of irreparable cuff tear, Yildiz et al demonstrated no significant differences between FLA and HDA grafts in terms of macroscopic healing rates, and subsequent biomechanical properties (failure loads, stiffness, and displacement) between FLA and HDA grafts.…”
Section: See Related Article On Page 2783mentioning
confidence: 99%
“…Regardless of the patient age or time after implantation, all grafts have shown evidence of cellular infiltration, neovascularization, and active remodeling. The results have also suggested that there is a relationship between implant duration and the extent of recellularization, as well as that human ADM materials can be successfully incorporated into host tissue when used in superior capsule reconstruction [67]. For example, Chu et al [68] grafted MSCs onto an ADM scaffold to treat diabetic cutaneous wounds, and found that the MSC-ADM treatment significantly increased angiogenesis and rapidly completed the re-epithelialization of newly formed skin on diabetic mice.…”
Section: Characteristics and Application Mechanism Of Admmentioning
confidence: 99%